1999
DOI: 10.1111/j.1651-2227.1999.tb01045.x
|View full text |Cite
|
Sign up to set email alerts
|

Duration of breastfeeding and developmental milestones during the latter half of infancy

Abstract: Several studies have suggested that breastfeeding has a long‐term influence on brain development. However, interpretation of these findings is complicated by the presence of many potential confounding factors. Only a few studies have examined infants before 1 y of age, although very early assessment might reduce the role of environmental influence. We investigated the association between exclusive breastfeeding and three developmental milestones related to general and fine motor skills and early language devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(37 citation statements)
references
References 28 publications
2
34
1
Order By: Relevance
“…Children who are not breastfed are at increased risk of respiratory tract infection, otitis media, diarrhea, necrotizing enterocolitis, undernutrition, and childhood overweight. [1][2][3][4][5][6] Maternal health risks associated with not breastfeeding include increased risk of postpartum blood loss, premenopausal breast cancer, and ovarian cancer. [7][8][9] Many medical and professional groups such as the World Health Organization, the United Nations Children's Fund, the American Academy of Obstetricians and Gynecologists, the American Academy of Pediatrics (AAP), and others advocate human milk as the gold standard for infant feeding.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Children who are not breastfed are at increased risk of respiratory tract infection, otitis media, diarrhea, necrotizing enterocolitis, undernutrition, and childhood overweight. [1][2][3][4][5][6] Maternal health risks associated with not breastfeeding include increased risk of postpartum blood loss, premenopausal breast cancer, and ovarian cancer. [7][8][9] Many medical and professional groups such as the World Health Organization, the United Nations Children's Fund, the American Academy of Obstetricians and Gynecologists, the American Academy of Pediatrics (AAP), and others advocate human milk as the gold standard for infant feeding.…”
Section: Methodsmentioning
confidence: 99%
“…10 Among the benefits attributed to feeding children human milk rather than substitutes such as infant formula are earlier or advanced language and motor skills development. 5,[11][12][13][14] Research findings, however, have been inconsistent; some studies find no effect from breastfeeding, 14 and others show beneficial effects on children's development attributable to breastfeeding or feeding children human milk. 5,13,15,16 In addition, previous studies suffered from limitations such as failing to control adequately for potential confounding variables, using a small sample size, 5 or focusing only on specific types of children, such as those in a certain age range 5,11,13 or twins, 14 thereby raising questions of generalizability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic, environmental, and social factors are important determinants of neurodevelopment (23,27). The slightly earlier language development among the children of the hairdressers may have been due to better environmental stimulation in early childhood, since the hairdressers had shorter workhours than the shop assistants.…”
Section: Zhu Et Almentioning
confidence: 99%
“…Studies that examined developmental time points have observed advantages of breastfeeding in comparison with not breastfeeding for infant development that can be observed from the neonatal period (Hart, Boylan et al 2003), through to infancy (Vestergaard, Obel et al 1999), early childhood (Fergusson, Beautrais et al 1982), midchildhood (Oddy, Robinson et al 2011), adolescence (Oddy, Kendall et al 2010) and into midlife (Richards, Hardy et al 2002). Some reviews and individual studies have found the protective effect of a longer duration of breastfeeding on child behaviour and cognition to be an artifact of sociodemographic confounding rather than a true association.…”
Section: Introductionmentioning
confidence: 99%